Upgrading and the geography of the Hungarian automotive industry in the context of the fourth industrial revolution - Molnár, Ernő; Kozma, Gábor; Mészáros, Márk; Kiss, Éva (Hungarian Geographical Bulletin, 2020)
The present study focuses on the geographical investigation of the automotive industry in Hungary that has been integrated into the global production networks as a relevant sector of the reindustrialization in East- Central Europe. The aim of the paper is to reveal the dominant spatial trends in this sector since the economic crisis of 2008, and how these are connected to the issue of upgrading influenced also by digitalization. The analysis is primarily based on the official industrial employment data however other secondary sources are also used. It has been stated that the growth of the Hungarian automotive industry showing to the direction of geographical concentration and expansion is accompanied by the regional stability of the sector. Quality indicators expressing upgrading indicate correlation with the spatiality of car factories and Tier 1 suppliers carrying out more complex activities, but a more significant functional upgrading is only realised in the capital city with increasingly research-development focused profile. Results suggest only moderate upgrading despite the gradual adaptation of Industry 4.0 technologies.